Inclusão social e atividades culturais: o Centro Cultural Banco do Brasil no Rio de Janeiro - Castro, Rodolfo Muanis Fernades de (2008)
The aim of this study is to look into the benefits provided to social inclusion by cultural activities carried out in a cultural place with great seriousness at Rio de Janeiro. To accomplish that, the author attempt to deepen into the social exclusion/inclusion in brazilian urban context, spotlighting the historic reality of the urban process of the city. Afterwards, by means of a quality research, document files from the cultural spot were consulted and looked into the view of customers, trustees and managers. For customers were applied questionnaires with open and close questions, with trustees and managers were made interviews, and also a documentary research with opinions available in mass media. This study fits into public politics, cultural and institutional marketing, for presenting examples of how cultural activities are essential tools for completely social inclusion of people in community, demonstrating that often marketing enterprises in culture area can result in benefits for society, even no being these their main purposes.